PSYCHIATRIC INVESTIGATION USING WGMs IN MICRORING CIRCUITS - KREANGSAK TAMEE; PREECHA P. YUPAPIN (My University, 2013)
The use of an electrical probe is formed by whispering gallery modes (WGMs) of light within the coated microring circuits, in which the electrical signal is generated by trapped electron tunneling along the circular path of the coated microring circuit. The collection of electrons is formed within the WGMs, where in this study, a modified nonlinear microring resonator known as a PANDA ring resonator is coated by gold material and forms the mirroring circuit. The induced current (magnetic field) within the circuit occurs by the coupling effects between trapped electrons and coated ring, which can penetrate into the brain cells and transform to the required signals via the terahertz carrier for psychiatric investigations. The use of WGMs for 3D image construction using a PANDA conjugate mirror is also discussed, which is useful for thermal and imaging sensors.
Keywords: SIGNAL (programming language); Photonic and Optical Devices